Comparing the Effect of Microinjection of Angiotensin II and Captopril to the Locus Coeruleus on Morphine Withdrawal Signs in Rat - Zohreh Azizolahi; Hojatollah Alaei; Mahmoud Hosseini; Ali Asghar Pilehvarian (مجله دانشکده پزشکی اصفهان, 2009)
Background: Locus coeruleus is one of important involved sites in morphine withdrawal signs, contains high densities of Angiotensin II receptor binding sites. In this study the effect of microinjection of Angiotensin II and captopril to the Locus coeruleus on morphine withdrawal signs was evaluated. Methods: Male wistar rats were anesthetized and stainless style cannula implanted in the locus coeruleus and allowed to recover from surgery. Morphine was injected 3 times in each day for 4 days to induce morphine dependence. The animals divided into 3 groups; control group received saline and case groups received Angiotensin II (1 nanomole) or captopril (30 µg) before naloxone injection. After naloxone injection, morphine withdrawal signs were assessed and compared between groups. Findings: In Angiotensin group, some of withdrawal signs such as wet dog shakes was significantly higher than saline group (P < 0.05). Expression of some of withdrawal signs such as jumping in Angiotensin group was decreased more than saline group (P < 0.01). Also, in captopril group some of withdrawal signs such as wet dog shakes was significantly higher than those of saline group (P < 0.05. Expression of some of withdrawal signs such as writhing posture, teeth chattering, grooming, genital grooming and head shakes were decreased in captopril group more than saline group (P < 0.05). Conclusion: We suggest that Angiotensin II have some roles in opioid withdrawal through locus coeruleus nucleous which contains considerable receptors for it.